2008
DOI: 10.1007/s10038-008-0294-y
|View full text |Cite
|
Sign up to set email alerts
|

G6PD deficiency assessment in Freetown, Sierra Leone, reveals further insight into the molecular heterogeneity of G6PD A-

Abstract: Glucose-6-phosphate dehydrogenase (G6PD) deficiency in Africa is of high prevalence, although precise data are lacking in many individual nations. We investigated 129 unrelated subjects (71 male subjects, 58 female

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 12 publications
2
14
0
Order By: Relevance
“…Besides the mutants described by Minucchi’s review [34], we include the following new variants: Class II G6PD Bahia (Phe66Thr, exon 4) [43], San Luis Potosi (Asn126Tyr; exon 5) [37], Coimbra (Arg198His, exon 6) [45], a class III variant with double mutation; G6PD Sierra Leone (Arg104His, Asn126Asp, exon 5) [46], a class IV G6PD San Paulo mutant (Ile220Met, exon 7) [47]. Finally, we found four mutants that did not classified according to their residual enzyme activity: G6PD Shanghai (Ala231Pro, exon 7) [48], G6PD Karachi (Asp325Asn, exon 9) [49], G6PD Vietnam 1 (Glu3Lys, exon 2) [50], and G6PD Vietnam 2 (Phe66Cys, exon 4) [50] which are shown in the Figure 4.…”
Section: Molecular Characterization Of G6pd Variantsmentioning
confidence: 99%
See 3 more Smart Citations
“…Besides the mutants described by Minucchi’s review [34], we include the following new variants: Class II G6PD Bahia (Phe66Thr, exon 4) [43], San Luis Potosi (Asn126Tyr; exon 5) [37], Coimbra (Arg198His, exon 6) [45], a class III variant with double mutation; G6PD Sierra Leone (Arg104His, Asn126Asp, exon 5) [46], a class IV G6PD San Paulo mutant (Ile220Met, exon 7) [47]. Finally, we found four mutants that did not classified according to their residual enzyme activity: G6PD Shanghai (Ala231Pro, exon 7) [48], G6PD Karachi (Asp325Asn, exon 9) [49], G6PD Vietnam 1 (Glu3Lys, exon 2) [50], and G6PD Vietnam 2 (Phe66Cys, exon 4) [50] which are shown in the Figure 4.…”
Section: Molecular Characterization Of G6pd Variantsmentioning
confidence: 99%
“…Jalloh et al [46] reported the Class III G6PD Sierra Leona variant, which has double mutation in exon 5 (311G > A and 376A > G) leading to the change of amino acid 104 Arg → His and 126 Asn → Asp, respectively. This mutation drastically reduces G6PD activity [46].…”
Section: Molecular Characterization Of G6pd Variantsmentioning
confidence: 99%
See 2 more Smart Citations
“…13 Although the G6PDd A− variant makes up the vast majority of G6PDd cases in most West African populations, there are other G6PDd mutations that do reach polymorphic levels in some populations. 14,15 Further studies should investigate the distribution of the A− variant in other parts of Haiti and include full G6PD gene sequence data with G6PDd phenotype data, to obtain a more complete picture of the genetic background of G6PDd in Haiti, as the severity of hemolytic anemia after primaquine exposure varies based on G6PDd genotypes. Additionally, more studies should follow response to primaquine treatment in G6PD A− individuals in Haiti to confirm that hemolytic anemia is not a high risk at the new recommended lower dose.…”
mentioning
confidence: 99%